Biomimetic tolerogenic artificial antigen presenting cells for regulatory T cell induction. (August 2020) - Rhodes, Kelly R.; Meyer, Randall A.; Wang, Justin; Tzeng, Stephany Y.; Green, Jordan J.
Abstract: Regulatory T cell (Treg)-based therapeutics are receiving increased attention for their potential to treat autoimmune disease and prevent transplant rejection. Adoptively transferred Tregs have shown promise in early clinical trials, but cell-based therapies are expensive and complex to implement, and "off-the-shelf" alternatives are needed. Here, we investigate the potential of artificial antigen presenting cells (aAPCs) fabricated from a blend of negatively charged biodegradable polymer (poly(lactic-co-glycolic acid), PLGA) and cationic biodegradable polymer (poly(beta-amino ester), PBAE) with incorporation of extracellular protein signals 1 and 2 and a soluble released signal 3 to convert naïve T cells to induced Foxp3+ Treg-like suppressor cells (iTregs) both in vitro and in vivo in a biomimetic manner. The addition of PBAE to the aAPC core increased the conjugation efficiency of signal proteins to the particle surface and resulted in enhanced ability to bind to naïve T cells and induce iTregs with potent suppressive function. Furthermore, PLGA/PBAE tolerogenic aAPCs (TolAPCs) supported the loading and sustained release of signal 3 cytokine TGF-β. A single dose of TolAPCs administered intravenously to C57BL/6 J mice resulted in an increased percentage of Foxp3+ cells in the lymph nodes. Thus, PLGA/PBAE TolAPCs show potential as an "off-the-shelf" biomimetic material for tolerance induction. Statement of Significance: Regulatory T cells (Tregs) are promising for basic research and translational medicine as they can induce tolerance and have the potential to treat autoimmune diseases such as type 1 diabetes and multiple sclerosis. As cell-based therapies are expensive and difficult to manufacture and implement, non-cellular methods of engineering endogenous Tregs are needed. The research reported here describes a new type of biomimetic particle, tolerogenic artificial antigen presenting cells (TolAPCs) fabricated from a blend of negatively charged biodegradable polymer, poly(lactic-co-glycolic acid), and positively charged biodegradable polymer, poly(beta-amino ester), along with key biomolecular signals: extracellularly presented protein signals 1 and 2 and a soluble released signal 3. These TolAPCs bind to naïve T cells and induce Foxp3+ Treg-like suppressor cells with potent suppressive function. In both in vitro and in vivo studies, it is shown that this non-cellular approach is useful to induce tolerance. Graphical abstract: Image, graphical abstract